Observations on "An unpublished and unknown review by Giacomo Leopardi ("L''ombra di Dante")" (Prassi Ecdotiche della Modernità Letteraria, 2022)
The short book by Christian Genetelli, An unpublished and unknown review by Giacomo Leopardi ("L'ombra di Dante") (Milan, LED-University Editions, 2020, Palinsesti series, directed by William Spaggiari), presents an unpublished paper by Giacomo Leopardi, escaped from the many scholars who have compulsory the poet's archive kept at the Vittorio Emanuele Library in Naples, or valued by them of little account. The ways in which Genetelli presents it deserve particular attention, at least for two reasons: a first, of course, relating to Leopardi, and a second because it exemplifies well the method of historical-philological investigation which, once again, is confirmed as being of great effectiveness for the knowledge of a text and its author.
Keywords: Giacomo Leopardi; attribution; authorship